A statistical study on the characteristics of ionospheric storms in the equatorial ionization anomaly region: GPS‐TEC observed over Taiwan. Issue 6 (21st June 2013) - Liu, J. Y.; Yang, W. H.; Lin, C. H.; Chen, Y. I.; Lee, I. T.
Abstract : [1] Positive and negative signatures of the ionospheric storms caused by the penetration electric field, disturbance dynamo, neutral wind, neutral composition, etc., have been reported. In this paper, the ionospheric total electron content (TEC) derived from the records of a network of ground‐based GPS receivers in Taiwan is used to statistically study the characteristics such as local time of appearance and duration of the storm signatures of various casuals in the equatorial ionization anomaly (EIA) region during 1994–2003. A bias‐corrected accelerated bootstrap method and a z test are employed for the first time to detect each event, and the overall storm signatures and characteristics, respectively. It is found that the positive signatures that appeared minutes to hours after the geomagnetic storm onset are pronounced on the storm day and the next day, while the negative signatures that started hours after the geomagnetic storm onset can last for as long as the next 4 days. The positive signature is statistically significant and most pronounced, when the intense geomagnetic storm onset occurs during local afternoon, which suggests that the signature may result from a combination of the prompt penetration electric field effect and mechanical effects of equatorward neutral wind. Additionally, the negative signature that is statistically significant and most pronounced in the local afternoon of the storm‐onset day and/or the next day may be produced by the disturbance dynamo or overshielding effects. The long‐lasting negative signature occurred in local midnight‐noon period on days 2–4 after the storm onset may result from the neutral composition disturbances. Key Points: Statistical studies of the duration of ionospheric storms Discriminate ionospheric storm effects A bias‐corrected accelerated bootstrap method and a z test analyses